Adjustment delays in production and the impact of cyclical shocks. (1st January 2000) - Cohen, Marcel; Shepherd, David
In this paper, we quantify an important management problem, which is how a company should respond to cyclical shocks of different amplitudes and duration when time delays are present in the factor input adjustment process. Our objective is to show how different shock profiles affect the amplitude and wavelength of the production path. We also consider the extent to which cyclical shocks generate long-run persistence in the time-path of output. Finally, our analysis suggests a scheme, which is not based simply on calendar time, for classifying different shock profiles as short or long.